P3.331 Prevalence of Chlamydia Trachomatis Infection and Associated Factors in Brazilian Pregnant Women: Preliminary Results of a Population-Based Study. (13th July 2013) - Mesenburg, M A; Stauffert, D; Silveira, M F
Abstract : Background: genital infections such as Chlamydia trachomatis are a serious public health problem worldwide and are related with several negative outcomes in the pregnancy as preterm birth. In Brazil there is a growing trend in preterm birth due to several factors. Despite the probability of association with this outcome and Chlamydia trachomatis infection, there is few Brazilian population-based studies on its prevalence and factors associated in pregnant women. This study aims to improve the knowledge about the current situation of Chlamydia trachomatis infection in pregnant women in Brazil. Methods: this is a cross-sectional study with pregnant women seen in all hospitals in the city of Pelotas, southern Brazil. Data was obtained from 361 pregnant women, bellow 30 years of age, interviewed between December 2011 and January 2013. Information on sociodemographic and behavioural factors were obtained through structured questionnaires and gestational age at delivery was obtained by medical examination. The status of Chlamydia infection was assessed by analysis of vaginal secretion, processed by Strand Displacement Amplification (SDA) BD ProbeTec™ system. Results: the prevalence of Chlamydia trachomatis infection was 15%. Pregnant women without steady partners were 2.2 times more likely to test positive to Chlamydia infection. We could not find statistically significant association between Chlamydia infection and the woman's age, smoking, alcohol use, drug use and preterm birth (gestational age ≤ 36 weeks). Conclusion: although preliminary, our results show that the prevalence of Chlamydia trachomatis among young pregnant women is high. Until the moment, we could not find association between infection and preterm birth, however it is necessary that the study be completed to better assess this relationship. Even thought our results contribute to reinforce the idea that routine test for Chlamydia trachomatis should be added to the recommended antenatal tests, at least for young pregnant women in Brazil.